The artificial loss of Runx1 reduces the expression of quiescence-associated transcription factors in CD4(+) T lymphocytes - Wong, W.F.; Kohu, K.; Nagashima, T.; Funayama, R.; Matsumoto, M.; Movahed, E.; Tan, G.M.Y.; Yeow, T.C.; Looi, C.Y.; Kurokawa, M.; Osato, M.; Igarashi, K.; et al. (2015)
The Runx1 transcription factor cooperates with or antagonizes other transcription factors and plays essential roles in the differentiation and function of T lymphocytes. Previous works showed that Runx1 is expressed in peripheral CD4(+) T cells which level declines after T cell receptor (TCR) activation, and artificial deletion of Runx1 causes autoimmune lung disease in mice. The present study addresses the mechanisms by which Runx1 contributes to the maintenance of peripheral CD4(+) T cell quiescence. Microarray and quantitative RT-PCR analyses were employed to compare the transcriptome of Runx1 -/- CD4+ T cells to those of unstimulated and TCR-stimulated Runx1 +I cells. The results identified genes whose expression was modulated similarly by Runx1 deletion and TCR activation. Among them, genes encoding cytokines, chemokines, and Jak/STAT signaling molecules were substantially induced. In Runx1-deleted T cells, simultaneous increases in Il-17A and Ror gamma c, a known master gene in T(H)17 differentiation, were observed. In addition, we observed that the loss of Runx1 reduced the transcription of genes encoding quiescence-associated transcription factors, including Foxp1, Foxo1, and Klf2. Interestingly, we identified consensus Runx1 binding sites at the promoter regions of Foxp1, Foxo1, and Klf2 genes, which can be enriched by chromatin immunoprecipitation assay with an anti-Runx1 antibody. Therefore, we suggest that Runx1 may activate, directly or indirectly, the expression of quiescence-associated molecules and thereby contribute to the maintenance of quiescence in CD4(+) T cells. (C) 2015 Elsevier Ltd. All rights reserved.